Prevalence of frailty and prefrailty among community-dwelling older adults in low-income and middle-income countries: a systematic review and meta-analysis. Issue 3 (1st March 2018) - Siriwardhana, Dhammika D; Hardoon, Sarah; Rait, Greta; Weerasinghe, Manuj C; Walters, Kate R
Abstract : Objective: To systematically review the research conducted on prevalence of frailty and prefrailty among community-dwelling older adults in low-income and middle-income countries (LMICs) and to estimate the pooled prevalence of frailty and prefrailty in community-dwelling older adults in LMICs. Design: Systematic review and meta-analysis. PROSPERO registration number is CRD42016036083. Data sources: MEDLINE, EMBASE, AMED, Web of Science, CINAHL and WHO Global Health Library were searched from their inception to 12 September 2017. Setting: Low-income and middle-income countries. Participants: Community-dwelling older adults aged ≥60 years. Results: We screened 7057 citations and 56 studies were included. Forty-seven and 42 studies were included in the frailty and prefrailty meta-analysis, respectively. The majority of studies were from upper middle-income countries. One study was available from low-income countries. The prevalence of frailty varied from 3.9% (China) to 51.4% (Cuba) and prevalence of prefrailty ranged from 13.4% (Tanzania) to 71.6% (Brazil). The pooled prevalence of frailty was 17.4% (95% CI 14.4% to 20.7%, I 2 =99.2%) and prefrailty was 49.3% (95% CI 46.4% to 52.2%, I 2 =97.5%). The wide variation in prevalence rates across studies was largely explained by differences in frailty assessment method and the geographic region. These findings are for the studies with a minimum recruitment age 60, 65 and 70 years. Conclusion: The prevalence of frailty and prefrailty appears higher in community-dwelling older adults in upper middle-income countries compared with high-income countries, which has important implications for healthcare planning. There is limited evidence on frailty prevalence in lower middle-income and low-income countries. PROSPERO registration number: CRD42016036083 .